2021
DOI: 10.1021/acsami.1c15772
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate-Assisted Route for Constructing Chalcogen Quantum Dots with Photoinduced Fluorescence Enhancement

Abstract: Despite great efforts in the development of diverse nanomaterials, a general route to synthesize metal-free chalcogen quantum dots (QDs) is still lacking. Moreover, the modification of chalcogen QDs is a bottleneck that severely hinders their applications. Herein, we develop a facile method to construct different chalcogen QDs (including S QDs, Se QDs, and Te QDs) with the assistance of thiolates. In addition to stabilizing chalcogen QDs, the thiolates also endow the chalcogen QDs with favorable modifiability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Despite impressive progress has been made in the past three years, neither the PLQY of SQDs nor the S-to-SQDs CE can meet the requirements of practical applications. For example, the PLQY of SQDs is still much lower than the traditional semiconductor quantum dots (generally >70%). On the other hand, although different reaction conditions were employed, almost all the reported methods are based on the reaction system of S-NaOH, in which a lot of S was converted into oxidation state of sulfur (e.g., SO 2 – and SO 3 2– ) and polysulfide ions (S x 2– ) instead of SQDs, ,, resulting in extremely low utilization of S. Furthermore, complete removal of these byproducts requires tedious purification procedures associated with high cost. Therefore, the direct utilization of S to scalable synthesis of SQDs with high PLQY has remained an enormous challenge.…”
Section: Introductionsupporting
confidence: 90%
“…Despite impressive progress has been made in the past three years, neither the PLQY of SQDs nor the S-to-SQDs CE can meet the requirements of practical applications. For example, the PLQY of SQDs is still much lower than the traditional semiconductor quantum dots (generally >70%). On the other hand, although different reaction conditions were employed, almost all the reported methods are based on the reaction system of S-NaOH, in which a lot of S was converted into oxidation state of sulfur (e.g., SO 2 – and SO 3 2– ) and polysulfide ions (S x 2– ) instead of SQDs, ,, resulting in extremely low utilization of S. Furthermore, complete removal of these byproducts requires tedious purification procedures associated with high cost. Therefore, the direct utilization of S to scalable synthesis of SQDs with high PLQY has remained an enormous challenge.…”
Section: Introductionsupporting
confidence: 90%
“…Typically, SeNPs exhibit well-defined and robust diffraction peaks at the 2𝜃 of 24°and 30°. [29,60] However, if the SeNPs are coated with polymer stabilizers like CS and CMC, the recognizable peaks of the SeNPs become remarkably feeble, [35,71] as demon- [26] Copyright 2015, Elsevier Inc. b) TEM image of small-sized SeNPs. Reproduced with permission.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Another synthesis strategy is called the top-down strategy, which is to synthesize fluorescent SQDs directly from elemental S through solution chemistry combined with different reaction conditions such as hydrothermal ( Xiao et al, 2019 ), ultrasonic ( Zhang et al, 2019 ; Zhang et al, 2021 ), and microwave ( Hu et al, 2020 ) treatment. For example, Shen et al first reported the preparation of fluorescent SQDs by the reaction of elemental S with NaOH in the presence of a polyethylene glycol (PEG) stabilizer ( Shen et al, 2018 ).…”
Section: Synthesismentioning
confidence: 99%